Optic nerve avulsion: A rare presentation of blunt trauma - Valiyaveettil Babitha; Chellappan Prasannakumary; ECK Ramesan; Kuzhippally Vlluon Raju (Wolters Kluwer Medknow Publications, 2017)
Optic nerve avulsion is one of the severe complications of blunt ocular trauma. Although a rare entity, optic nerve avulsion should be suspected in all blunt trauma cases presenting with sudden marked visual loss accompanied with dense vitreous hemorrhage.